Rapid mangrove expansion triggered by low river discharge episode in Nanliu river estuary, Beibu Gulf of China - Liu, Tao; Huang, Rongyong; Sun, Yonggen; Liu, Ying; Song, Zhiguang (Frontiers in Marine Science, 2024)
Mangrove forest is a critical primary producer, biological habitat, and carbon sink in the subtropical-tropical coast zone, and the natural variation of mangrove coverage deserves study for a better understanding of the dynamics of mangrove coastal evolution. In this study, multispectral Landsat images from 1985 to 2018 are used to reconstruct the change in the coverage of mangrove (dominant species is Aegiceras corniculatum) and salt marsh (dominant species is Cyperus malaccensis) in the Nanliu River estuary. Tidal flat elevation measuring and 210Pb dating is used to study the substrate elevation when mangroves first colonize salt marsh. Historical temperature records, river discharge records, and the time series N/P concentration in sediment are analyzed. It is found that the mangrove forests have expanded rapidly in salt marsh since the mid-1980s. The change in factors such as accommodation space, cold event frequency, and nutrient supply cannot explain the origin of mangrove expansion. A low river discharge episode lasting for 8 years since 1986 is considered to have triggered the mangrove expansion in this area, as previously established salt marsh plants died due to germination restriction caused by high salinity and mangroves colonized the salt marsh habitat during this period. This case proves again that estuarine wetlands are very sensitive to salinity variation.